Therapeutic Group Therapy on the Ability of Parents to Stimulate Social and Emotional Development in Preschool Age Children at Dharma Wanita Kindergarten Tosaren II Kediri City - Dhita Kurnia Sari; Farhan Nur Arif; Lingga Kusumawardani; Dedi Saefullah (Jurnal Ilmu Keperawatan Jiwa, 2023)
The knowledge and ability of parents in providing stimulation for pre-school age children is very important to have, because pre-school age is a critical period for children who need stimulation for growth and development. Therapeutic group therapy is a promotive action to improve child development to be optimal. This study uses a pre-experimental design research with a one grub pretest-posttest design approach. This research was conducted at Dharma Wanita Tosaren II Kindergarten with a population of 65 people. The technique of determining the sample uses a purposive sample technique, namely by determining certain criteria. Data were collected using a questionnaire sheet, bivariate analysis using the Paired Sample T-Test with the help of SPSS. Based on statistical tests, it is known that the value of sig. (2-tailed) of 0.000 < 0.05, it can be concluded that there is a significant difference between the ability of parents to stimulate children's development before and after group therapy is difficult. So that therapeutic group therapy can be applied in increasing the ability of parents to stimulate the development of pre-school age children well and can be maximized. Keywords: Parental Ability, Stimulation of Children's Social and Emotional Development, Therapeutic Group Therapy.